2019
DOI: 10.3390/e21121193
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Condition Monitoring Decision Making by the Criterion of Minimum Entropy

Abstract: Condition-based maintenance (CBM) is a promising technique for a wide variety of deteriorating systems. Condition-based maintenance’s effectiveness largely depends on the quality of condition monitoring. The majority of CBM mathematical models consider perfect inspections, in which the system condition is assumed to be determined error-free. This article presents a mathematical model of CBM with imperfect condition monitoring conducted at discrete times. Mathematical expressions were derived for evaluating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The maintenance effectiveness indicator was the expected cost per regeneration cycle. Studies [53,54] have shown that the probabilities of imperfect inspections at condition-based and predictive maintenance are functions of the degradation model parameters and strongly depend on time. In the study [55], the case of imperfect testing of the crack depth in a fighter wing was considered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The maintenance effectiveness indicator was the expected cost per regeneration cycle. Studies [53,54] have shown that the probabilities of imperfect inspections at condition-based and predictive maintenance are functions of the degradation model parameters and strongly depend on time. In the study [55], the case of imperfect testing of the crack depth in a fighter wing was considered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is currently an increased research interest in aircraft maintenance optimization since it directly impacts system availability and operational costs [42]. The main aircraft maintenance optimization techniques that have been researched recently are based on aircraft maintenance service scheduling, spare parts inventory, and aircraft maintenance planning.…”
Section: Related Workmentioning
confidence: 99%